ANALYSIS OF INCOME AND WELFARE LEVEL OF THE RAP TAMA JAYA FOREST FARMERS GROUP (KTH) IN RONGGURNIHUTA VILLAGE, SAMOSIR REGENCY, NORTH SUMATRA PROVINCE - Jesika Naibaho; Ahyauddin Ahyauddin; Rince Muryunika (Sylva Jurnal Ilmu-ilmu Kehutanan, 2025)
Social forestry is one of the government strategies for sustainable forest management by involving local communities as the main actors. One of its implementations is granting forest utilization access through the Community-Based Forest Management (HKm) scheme. KTH Rap Tama Jaya in Ronggurnihuta Village, Samosir Regency, is one of the groups receiving such utilization rights, focusing on the utilization of non-timber forest products (NTFPs) such as pine resin, honey, and citronella across a management area of 375 hectares. This study aims to analyze the income of KTH members and their welfare level based on the BPS indicators, as well as to examine the relationship between income and welfare levels of KTH Rap Tama Jaya members. Data were analyzed using descriptive quantitative methods through the calculation of revenue, costs, income, R/C ratio, and Pearson Product Moment correlation test. The results showed that the average income of KTH members was Rp23,166,274/year with an R/C ratio value of 21.2, indicating that the NTFP-based enterprises are feasible to be developed. The welfare analysis showed that 81.13% of members were categorized as prosperous. Furthermore, the correlation analysis showed a coefficient value of r = 0.618 with t value of 5.615 > t table of 2.008, indicating a positive and significant relationship between income and welfare levels of KTH Rap Tama Jaya members.